A educação ambiental como apoio ao manuseio e tratamento dos resíduos sólidos em comunidades ribeirinhas: estudo de caso em Abaetetuba-PA - SANTOS, Albenita Ribeiro dos (Universidade Federal do Pará, 2019)
One of the major environmental concerns of contemporary society is the consequences that excessive consumption of products of industrial origin has on nature, especially the destination given after their use, this concern is observed in both urban and rural areas. The Abaetetuba-PA riverside communities are among those facing serious problems in the disposal of solid waste, giving them convenient but inadequate treatment. In this sense, this work was carried out in public schools of three riverside communities in the city, from January to December 2018, whose objective was to analyze the practice of Environmental Education as a motivator of sustainable actions regarding the proper use and handling of waste. solid. The research is qualitative and quantitative and participated in the work students of 8th and 9th grade of elementary school. Questionnaires were applied and pedagogical practices were developed, such as lectures, extracurricular activities, workshops and the elaboration of an environmental education booklet. The results were positive and are presented through graphs and tables. It was found that, before the activities, more than half of the students of the three schools, about 70%, were unaware of concepts such as sustainability, environmental education, solid waste, among others, and found the correct destination that their community was giving to household waste, as well as certain old practices of the population such as burning of waste. After the pedagogical activities we can notice the change of mentality in these students. With the knowledge acquired and through the introduction of environmental education, 90% of students thought and acted in a sustainable manner, even condemning any practice that could endanger the environment and their quality of life. Thus, they began to look for alternatives that could alleviate the consequences of improper disposal of solid waste. In addition, they began to bring information from their relatives and those interested in the topic, which until then was known to few. With this, they become multipliers of sustainable actions, contributing to the maintenance of their quality of life. Through an interview with the representative of the Secretariat of the Environment, we learned about projects aimed at minimizing the problem of solid waste disposal on the Abaetetuba Islands and the environmental booklet contributed to promote reflection and motivate the student to new ecological practices. The expected result is that new booklets will be produced and worked with students from all grades in both urban and rural areas of other municipalities and thus expand the practice of environmental education for the protection and preservation of the environment.